Efeito antipsicótico da associação da clorpromazina e ácido lipóico em modelo de esquizofrenia induzido pela cetamina em ratos - Sampaio, Luis Rafael Leite (2016)
Schizophrenia, a neuropsychiatric syndrome characterized by brain functions impairment, presents besides the behavioral symptoms, electroencephalographic changes and it is associated with a dysregulation of immune responses and oxidative component. However, the role of the inflammatory and oxidative damage on the electroencephalographic alterations present in schizophrenia was not completely clarified. Thus, this study aimed to investigate the electroencephalographic, behavioural and neurochemical effects in the hippocampus of rats treated with chlorpromazine alone or associated with lipoic acid in the model of schizophrenia induced by ketamine. However, the role of oxidative damage in electroencephalographic changes present in schizophrenia is not fully understood. As a result, this study aimed to evaluate the effects of the antipsicotics association of chlorpromazine (CP) and lipoic acid (ALA) in the schizophrenia model induced by ketamine (KET) in rats. Wistar male rats (200-300 g) were tested. They were treated for 10 days and divided into two experimental protocols: At first the animals were divided into 4 groups (n = 10) and treated with saline (control) or ketamine (10, 50, or 100 mg/kg). In the second, the animals were divided into 9 groups (n = 10) treated with saline (control), lipoic acid (100mg/kg), ketamine (10mg/kg) and chlorpromazine (1 or 5 mg/kg) alone or and ketamine (CP1 and CP5+KET) or associated with lipoic acid (ALA+CP1 and CP5+KET). For the electroencephalogram (EEG), the animals underwent a stereotactic surgery for the implantation of an electrode in the right hippocampus and were treated for 10 consecutive days. The brain waves were captured at 1 or 10 days for the groups treated only with Ketamine alone and on the 1st, 5th or 10th day to the groups treated with chlorpromazine alone or in combination with ketamine with or without lipoic acid. Tests were performed on 8 day (open field test and in the Y maze) and 10 day treatment (prepulse inhibition - IPP and neurochemical tests). Our results showed that administration of ketamine (10, 50 or 100 mg/kg) induced changes in the average spectral power of hippocampal delta, theta, alpha, gamma low and gamma high bands after acute or repeated treatment. The chlorpromazine alone or associated with ALA reversed the changes promoted by KET10 for hippocampal oscillations of the delta, gamma low and gamma high bands. Moreover, ketamine induced hyper locomotion changed the working memory and increased IPP, and these effects reversed by pretreatment of chlorpromazine alone or association with ALA. Moreover, ketamine administration decreased GSH, increased nitrite, lipid peroxidation and the concentration of MPO. These effects by KET were reversed chlorpromazine and enhanced by the ALA when associated with CP1. In conclusion, treatment with ketamine in mice promotes behavioral, neurochemical, and electroencephalographic changes in the hippocampus and these changes may be related with the hypofunction of NMDA receptors in the glutamatergic system and chlorpromazine alone or associated with lipoic acid promotes the reversal of these effects, showing a beneficial activity as neuroprotective.